Design of Brushless DC Motor Driver Based on Bootstrap Circuit - Khoirudin Fathoni; Esa Apriaskar; Nur Azis Salim; Vera Noviana Sulistyawan; Rifki Lukman Satria; Syahroni Hidayat (Jurnal Elektronika dan Telekomunikasi, 2023)
Brushless DC (BLDC) motor is a three-phase motor that cannot work directly with DC current but requires electronic commutation to replace the brush function in DC motor. This paper aims to implement BLDC motor driver integration based on bootstrap circuit using Autodesk Eagle. The driver board consist of bootstrap circuit based on IR2110, MOSFETs, three voltage regulator, ESP32 microcontroller and ACS712 current sensor connection, logic level converter, and BLDC hall effect signal sensor conditioning. The research proposes bootstrap capacitor calculation based on charging/discharging capacitor principle and the minimum motor speed rotation. The implemented driver has 14x10 cm dimension tested to drive 24V/135W/6000rpm sensored BLDC motor using six steps commutation with pulse width modulation (PWM) inserted programmatically in ESP 32 to drive the high side MOSFET of the driver without AND gate circuit. The effect of pwm frequency and dutycycle variation to the speed and current of the motor is investigated. The results showed that the driver with both 12 V and 24 V voltage source and 68 μF bootstrap capacitor work optimally in 20 KHz PWM frequency both in open loop and closed loop speed control test. The motor reach 129 W for the largest power and 5250 rpm for the fastest speed in 24 V supply.